An Electrochemical Aptamer-Based Sensor for Real-Time Monitoring of Insulin - Wu, Yao (ACS Sens, 2019)
In this manuscript, we developed an electrochemical, aptamer-based (E-AB) for th real-time monitoring of insulin. The sensor utilizes a redox label-modified guanine-rich aptamer which folds into a G-quadruplex for specific recognition of insulin. To develop a reproducible E-AB sensor employing insulin aptamer probes for the detection of insulin, 10% sodium dodecyl sulfate (SDS) pretreatment is crucial as it disrupts interstrand G-quartets. After sensor pretreatment with 10% SDS, more uniform sensor response is obtained. Upon introduction of insulin target, binding-induced steric hindrance quantitatively reduces the efficiency of electron transfer of a distal-end redox label leading to the rapid signal change within ~60 s. Testing demonstrates that the E-AB insulin exhibits a limit of detection of 20 nM and can be used to discriminate against both glucagon and somatostatin in Krebs−Ringer bicarbonate buffer, typically used in perfusion experiments. These results demonstrate that this assay has potential for rapid, specific, and quantitative analysis of insulin.